Reduced growth sensitivity to water availability as potential indicator of drought-induced tree mortality risk in a Mediterranean Pinus sylvestris L. forest - Herrero, Asier; González-Gascueña, Raquel; González-Díaz, Patricia; Ruiz-Benito, Paloma; Andivia, Enrique (Frontiers in Forests and Global Change, 2023)
Introduction Drought-associated tree mortality has been increasing worldwide since the last decades, impacting structure and functioning of forest ecosystems, with implications for energy, carbon and water fluxes. However, the understanding of the individual vulnerability to drought-induced mortality is still limited. Methods We aimed to identify the factors that triggered the mortality of the widely distributed Pinus sylvestris L. in an extensive forest area in central Spain. We compared radial growth patterns in pairs of alive and recently dead individuals that co-occur in close proximity and present similar age and size, thereby isolating the effects of size and environment from the mortality process. Temporal dynamics of growth, growth synchrony, and growth sensitivity to water availability (precipitation minus potential evapotranspiration) were compared between alive and recently dead trees. Results and discussion Over the last 50 years, although we did not detect significant differences in growth between alive and dead trees, an increase in the growth synchrony and sensitivity to water availability (i.e. slope of the climatic water balance in the growth model) was observed in all trees as drought intensity increased. 20 years before mortality, dead individuals showed lower growth synchrony and growth sensitivity to water availability than alive ones, without significant differences in growth. Recorded reduction in growth synchrony and growth sensitivity to water availability in dead trees suggests a decoupling between tree growth and climate, which could increase the risk of hydraulic failure and/or carbon starvation under increasingly arid conditions. Thus, the use of reduced growth sensitivity to water availability as potential early-warning signal of tree mortality, together with reduced growth synchrony, should be further explored, particularly in pine species in seasonally dry areas.